Charles A. Kupchan's Isolationism - Tőke, Márton (AMERICANA E-journal of American Studies in Hungary, 2020)
KUPCHAN, Charles A. Isolationism – A History of America’s Efforts to Shield Itself From the World. New York: Oxford University Press, 2020.